Evaluation of research ethics committees in Turkey. Issue 6 (1st December 2000) - Arda, Berna
Abstract : In Turkey, there was no legal regulation of research on human beings until 1993. In that year "the amendment relating to drug researches" was issued. The main objectives of the regulation are to establish a central ethics committee and local ethics committees, and to provide administrative control.There are no compulsory clinical ethics lectures in the medical curriculum, so it is also proposed that research ethics committees (RECs) play a central educational role by helping physicians to be aware of moral problems and by contributing to the training of research teams.